The Sources of Laughter in The Novel Mürebbiye: Forms, Gestures and Movements - Ahmet, C. A.N. (Hacettepe University, 2023)
Humor has a prominent place in the novelism of Hüseyin Rahmi Gürpınar, who focuses on issues such as philosophy, family, wrong westernization, education and women in his novels. Gürpınar used characters and plots intensively to create humorous elements in his works. This study, which tries to determine the source of comic elements in Hüseyin Rahmi Gürpınar's novel Mürebbiye, is centered on the approach to laughter based on forms, gestures, and movements conceptualized by Henri Bergson in the first chapter of his work Laughter. Bergson, while explaining the concept of laughter, has positioned these concepts on the essential dynamics of social life. From this point of view, Hüseyin Rahmi Gürpınar's novel Mürebbiye's emphasis on the family and distorted human relations and its connection with the social situation is notable. In the novel, the narrator describes the comic situations created by forms, gestures, and movements by using similes and taking these situations to extremes. This study aims to evaluate the comic elements created by the narrator in the focus of people and plots regarding forms, gestures, and movements. © 2024 Elsevier B.V., All rights reserved.
MÜREBBİYE ROMANINDA GÜLÜNCÜN KAYNAKLARI: BİÇİMLER, JESTLER VE DEVİNİMLER*
Keywords: Comic; Forms; Gestures; Movements; Mürebbiye; Novel